Epidemiological Pattern of Head Injuries in Road Traffic Accident Victims Presenting to a Tertiary Care Hospital in South India - Shilpa Pateria, Rajesh Kamath2 ,Vikram Palimar3 , Harshith L.K4 , Biju Soman5 , Vishnu Sagar4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: In 2017, Karnataka registered 10,609 deaths due to Road Traffic Accidents (RTAs). Amongall injuries, head and especially brain injuries were responsible for significant mortality and morbidity.RTAs account for a significant proportion of brain injuries. Materials and Methods: Of 1035 cases of headinjuries visiting the trauma center of a tertiary care teaching hospital in south India, 650 head injuries wereattributable to RTAs during the period between August 1, 2017 to July 31, 2018. Retrospective data wasobtained from patient records taken from the medical records. After obtaining ethical approval, the recordswere analyzed in terms of age group variables, sex, time, day, season, accident event, means of transport,the practice of protective devices usage such as a helmet for 2 wheeler RTA victims and safety belt for 4wheeler RTA victims, insurance status, type of head injury: external or internal and diagnosis. Results:The incidence of RTAs was higher in males (77.3%), younger age group: 20 to 30 years (30.15%), drivers(48.31%), rainy season (40%), afternoon hours (38%) and weekdays (69.23%). Usage of protective deviceswas low (13.54%).